Real World Experience With Natalizumab at a Tertiary Care Pediatric IBD Center. Issue 6 (June 2016) - Singh, Namita; Deshpande, Rasika; Rabizadeh, Shervin; Dubinsky, Marla
ABSTRACT: Objectives: Natalizumab is a humanized monoclonal antibody inhibiting lymphocyte migration and prescribed in patients with Crohn disease (CD) failing anti-tumor necrosis factor (TNF) therapies. Because of the risk of progressive multifocal leukoencephalopathy in patients with John Cunningham virus (JCV) positive, natalizumab is not widely used in clinical practice. Published experience of the use of natalizumab in pediatric patients is lacking. We aimed to describe the experience of natalizumab in patients with CD, including those who are JCV positive, at a tertiary care pediatric inflammatory bowel disease center. Methods: A retrospective chart review was performed in patients with CD <21 years receiving natalizumab therapy before March 2014. Patient and disease information, prior treatments and response to natalizumab, including Harvey Bradshaw Index (HBI), were recorded. Descriptive statistics were computed. Results: Nine patients received natalizumab with a median age at diagnosis of 10 (range 7–16) years and median disease duration 72 (range 13–156) months. All of the patients had failed at least 1 anti-TNF agent. At baseline, the median HBI was 8 (IQR 6.5–11). By week 10, the median HBI was 4.5 (IQR 2–6), with 4 of 8 (50%) patients with CD being in remission. Forty-four percent (4/9) of patients were JCV antibody positive at baseline and had anti-JCV antibody index >0.9 (median 3.36). There were no serious adverse events, including progressive multifocal leukoencephalopathy. All of the patients were transitioned to vedolizumab. Conclusions: In our experience, natalizumab is a safe and efficacious medication in pediatric in patients with inflammatory bowel disease. Given the favorable results with natalizumab, pediatric studies with the more gut targeted anti-integrin agent vedolizumab are warranted.